2011
DOI: 10.1111/j.1708-8305.2011.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Respiratory Viruses Among Pilgrims in Saudi Arabia During the Time of a Declared Influenza A(H1N1) Pandemic

Abstract: We found very low pandemic influenza A(H1N1) prevalence among arriving pilgrims and no evidence that amplification of transmission had occurred among departing pilgrims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 20 publications
10
79
0
Order By: Relevance
“…Memish and colleagues reported that lack of awareness and knowledge about the access to vaccine were the two most important reasons for not receiving seasonal influenza vaccine among international pilgrims during the Hajj 2009. 8 Misperceptions about pandemic influenza vaccine have also been reported among health care workers (HCWs) deployed at Hajj in 2009 when over half refused the vaccine mainly because of a belief that pandemic influenza was not fatal and there were toxic preservatives in the vaccine. 28 In a previous survey conducted among Asia-Pacific travelers including Australians, 27% believed that they were not at risk of influenza and another 14% thought that influenza vaccine was not important.…”
Section: Discussionmentioning
confidence: 99%
“…Memish and colleagues reported that lack of awareness and knowledge about the access to vaccine were the two most important reasons for not receiving seasonal influenza vaccine among international pilgrims during the Hajj 2009. 8 Misperceptions about pandemic influenza vaccine have also been reported among health care workers (HCWs) deployed at Hajj in 2009 when over half refused the vaccine mainly because of a belief that pandemic influenza was not fatal and there were toxic preservatives in the vaccine. 28 In a previous survey conducted among Asia-Pacific travelers including Australians, 27% believed that they were not at risk of influenza and another 14% thought that influenza vaccine was not important.…”
Section: Discussionmentioning
confidence: 99%
“…To date only two quantitative studies have attempted to identify the reason behind lack uptake of vaccines. These studies found lack of vaccination knowledge and relay in body immunity associated with poor uptake of influenza vaccine [10,15]. Neither study explored the reasons underpinning these low rates of uptake and knowledge in any depth.…”
Section: Introductionmentioning
confidence: 85%
“…This low coverage could result from misperceptions surrounding the influenza vaccine. Lack of awareness and access to vaccination were the two most important factors in influenza vaccine refusal among pilgrims in a large study involving a considerable proportion of Saudi Arabian pilgrims [27]. Misperceptions are also reported among Australian Hajj pilgrims; for example, respectively 33% and 26% of the Australian pilgrims who reported not receiving influenza vaccine in 2011 and 2012 claimed to have relied on "natural immunity" [19].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…In a large crosssectional study conducted at King Abdulaziz International Airport in 2009, Memish et al. reported the uptake of influenza vaccine to be 22.9% [27]. Three additional studies were conducted in 2010 with the reported vaccination rate to be ranging from 26.9%…”
Section: Influenza Vaccine Uptakementioning
confidence: 97%
See 1 more Smart Citation